FT-IR Study of Effect of Chromium on Tissue Protein of an Edible Fish Cirrhinus mrigala - KARTHIKEYAN, S.; RM. PALANIAPPAN, PL.; SABHANAYAKAM, SELVI (Asian Journal of Chemistry, 2010)
Fourier transform infrared spectroscopy (FT-IR) is a powerful technique for molecular conformations of proteins, lipids and nuclei acids as well an interaction of the complex materials comprising biological tissues. The present study is aimed to investigate the effect of chromium on tissue protein of an edible fish by FT-IR Technique. The spectra revealed significant differences in band intensities and intensity ratios between treated and control groups. A significant decrease in the protein content was observed in treated samples compared to the control. The amide I band observed at ca. 1657 cm-1 indicate that the protein is dominated by α-helical structure.